Effect of laparoscopic splenectomy on portal haemodynamics in patients with liver cirrhosis and portal hypertension. Issue 12 (9th September 2014) - Kawanaka, H; Akahoshi, T; Kinjo, N; Iguchi, T; Ninomiya, M; Yamashita, Y-I; Ikegami, T; Yoshizumi, T; Shirabe, K; Maehara, Y
Abstract: Background: The effect of splenomegaly in patients with liver cirrhosis and portal hypertension is not fully understood. This study was designed to determine the effect of laparoscopic splenectomy on portal haemodynamics in these patients. Methods: Patients with liver cirrhosis and portal hypertension who underwent laparoscopic splenectomy in Kyushu University Hospital from January 2006 to March 2009 were evaluated retrospectively. Correlations between splenic size and portal haemodynamics, and changes in portal haemodynamics and in levels of the vasoactive agents endothelin (ET) 1 and nitric oxide metabolites (NOx) before and 7–10 days after laparoscopic splenectomy were analysed. Results: Portal venous (PV) blood flow, PV cross-sectional area and PV congestion index correlated significantly with splenic size ( P < 0·050). All three were significantly reduced following splenectomy in 59 patients. The hepatic venous pressure gradient, measured in 18 patients, decreased by 25 per cent after splenectomy ( P < 0·001). Portal vascular resistance was also reduced, by 21 per cent ( P = 0·009). The peripheral blood concentration of ET-1 decreased from 2·95 to 2·11 pg/ml ( P < 0·001), and that of NOx tended to decrease (from 29·2 to 25·0 pg/ml; P = 0·068). In hepatic venous blood, the level of ET-1 decreased from 2·37 to 1·83 pg/ml ( P = 0·006), whereas NOx concentration tended to increase (from 24·5 to 30·9 pg/ml; P = 0·067). Conclusion: In patients with liver cirrhosis and portal hypertension, splenectomy reduced portal venous pressure. A decrease in splanchnic blood flow, by eliminating splenic blood flow, and reduction in intrahepatic vascular resistance, by normalizing hepatic concentrations of ET-1 and NOx, may both have contributed. Abstract : Splenectomy improves splanchnic haemodynamics